PENGARUH PENGGUNAAN MEDIA FILM TERHADAP KEMAMPUAN MENULIS TEKS DESKRIPSI SISWA KELAS VII SMP AL-AZHAR MEDAN - Wita Dwi Payana (Jurnal Bahastra, 2020)
This study aims to determine the effect of using film media on the ability to write descriptive text of class VII SMP Al-Azhar Medan. The population of this study amounted to 103 students of SMP Al-Azhar Medan. Samples were taken randomly, namely the experimental class of 32 students. The method used in this study is an experimental one-group pre-test post-test design method. The instrument used to collect data is an essay test. Hypothesis testing is done by using the "t" test.               From the data obtained, it shows that the students' ability to write descriptive texts before using film media is included in the sufficient category with the average score (mean) obtained by students is 65.87, while the students ability to write descriptive texts after using film media is included in the good category with the average value (mean) obtained by students is 75.90. Furthermore, hypothesis testing shows tcount (3.47) ttable (2.04) at a significant level = 0.05. Thus Ho is rejected and Ha is accepted, meaning that there is an influence of film media on the ability to write descriptive texts for seventh grade students of SMP Al-Azhar Medan.            This shows that the results of learning to write descriptive text after using film media are better than learning outcomes before using film media, and the learning process after using film media has a positive effect on the ability to write descriptive text.